Development of new heat exchanger design for the use of exhaust gases of ice in cogeneration plants. heat calculation - Gorobets, V.; Trokhanyak, V.I.; Antipov, I.; Gorobets, Yu. (Energy and Automation, 2025)
A new design of a heat exchanger for the use of exhaust gases of an internal combustion engine, which is part of a cogeneration plant, is proposed.  This exchanger differs from traditional designs by the presence of compact bundles of small diameter pipes with no gaps between adjacent pipes in the longitudinal direction of the gas coolant movement. A method of heat calculation of heat exchanger-utilizer has been developed, which makes it possible to determine the dimensions of heat exchanger. The results obtained have been analyzed and it has been shown that the new design of heat exchanger-utilizer has a number of advantages compared to the known designs of shell-and-tube heat exchangers. It has been found that the new design of heat exchanger improves the mass-dimensional indicators of heat exchanger-utilizer compared to known designs and can be used in the development of cogeneration plants based on internal combustion engines.Key words: shell-and-tube heat exchanger, method calculation, heat calculation, design, cogeneration plant, tube bundle